(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Korolsky V. V. Kapіnosov A. M. Algorithmic mathematical competence: theoretical and methodological basis for the formation, structure and levels. The article presents theory-and-methodological bases for the formationof algorithmic competenceas a type of mathematical competence is closed its structure and levels.